2021
DOI: 10.2147/ndt.s311207
|View full text |Cite
|
Sign up to set email alerts
|

Periventricular White Matter Hyperintensity in Males is Associated with Post-Stroke Depression Onset at 3 Months

Abstract: Objective This study aimed to explore the correlation between white matter hyperintensity (WMH) and post-stroke depression (PSD) at 3 months, and to further investigate sex differences in the pathogenesis of PSD. Methods A total of 238 consecutive patients with acute cerebral infarction were recruited. PSD was assessed at 2 weeks and at 3 months after stroke onset. All stroke cases were divided into four subgroups according to the diagnosis of depression at two time nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Females need to focus on family life and social work, they may bear more stress. Many studies have found that the incidence of PSD in females is higher than that in males [9,10], and some studies reported that the incidence of PSD in females is similar to or significantly lower than that in males [11][12][13]. Perhaps because of inconsistencies in sample size, race, or time of evaluation, there is no consistent conclusion about the sex difference in the incidence of PSD, this study explores this and hopes to provide reference for future research.…”
Section: Introductionmentioning
confidence: 86%
“…Females need to focus on family life and social work, they may bear more stress. Many studies have found that the incidence of PSD in females is higher than that in males [9,10], and some studies reported that the incidence of PSD in females is similar to or significantly lower than that in males [11][12][13]. Perhaps because of inconsistencies in sample size, race, or time of evaluation, there is no consistent conclusion about the sex difference in the incidence of PSD, this study explores this and hopes to provide reference for future research.…”
Section: Introductionmentioning
confidence: 86%
“…Several studies have evaluated the pathophysiology, treatment, and prognosis of PSD. Particularly, several risk factors related to PSD were proposed, mainly focusing on clinical and laboratory factors such as Barthel index, female sex, diabetes mellitus, smoking, and white matter hyperintensity [7][8][9][10]. However, the psychiatric problem is the result of the complex action of not only the patient factors but also environmental factors.…”
Section: Introductionmentioning
confidence: 99%